STUDY OF OXIDATION RATE OF SULPHIDE MINERALS IN COAL MINING BASED ON LABORATORY KINETIC TEST RESULT. - Rianti, Lina
Kinetic test of geochemical has a function to affirmation static test results, but also determine the relative rate of sulphide minerals weathering by oxidation reaction. Therefore, the studies in this research will analyze the oxidation rate of sulphide minerals that contained in some rocks based on kinetic test result at the laboratory. By the analyzes, the oxidation rate of sulphide minerals could be understood as a complex of various aspects that influence it. Based on some parameters of data of leachate physical and chemical quality results by kinetic test, which we called Free Draining Column Leach Test (FDCL), on daily cycle, a cycle of 3 days, weekly cycle, and additional data such as static results and also mineralogy test results. Further more, the oxidation rate of sulphide minerals is analyzed by the release of sulphate, transfer mole of pyrites, and leachate physical quality (Oxidation Reduction Potential, pH, Total Dissolved Solid, Conductivity). The research results are the oxidation of sulphide minerals in the rocks that influenced by sulphate quality, metals quality, pH, sulphide minerals transfer mole, Oxidation Reduction Potential, Total Dissolved Solid, and Conductivity. On each cycle of kinetic test, it give different rates that influenced by some factors, such as the sustainable of every cycle, the same volume of water distillate, pause watering, oxygen that come in to the rocks, and the sulphide minerals remaining in the rocks. Based on the results, a cycle of three days kinetic test was running optimally enough, and it could be used to explain the stability of oxidation rate of sulphide minerals. Besides, one of samples characteristic show that the average oxidation rate of sulphide minerals in the rocks on daily cycle is 0,410 gr/day, on three days cycle is 0,380 gr/three days, and on weekly cycle is 0,310 gr/week.